2004
DOI: 10.1001/archinte.164.10.1108
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Thresholds for Pharmacological Intervention to Prevent Fractures

Abstract: Using peripheral measurement devices, 82% of postmenopausal women with fractures had T scores better than -2.5. A strategy to reduce overall fracture incidence will likely require lifestyle changes and a targeted effort to identify and develop treatment protocols for women with less severe low bone mass who are nonetheless at increased risk for future fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
517
2
25

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 924 publications
(577 citation statements)
references
References 304 publications
(367 reference statements)
18
517
2
25
Order By: Relevance
“…3, Table 1) revealed that approximately one-third of overweight and obese Americans age 45 and older have low bone mass (total hip BMD between 1 and 2.5 SD below the young reference mean), and many osteoporotic fractures occur at those levels of BMD. (64,65) Within these higher BMI categories, the prevalence of osteoporosis and low bone mass was higher in women than men and higher in whites and Mexican Americans than in African Americans (Fig. 3).…”
Section: Low Bmd As a Risk Factor For Fracture In Those With High Bmimentioning
confidence: 97%
See 1 more Smart Citation
“…3, Table 1) revealed that approximately one-third of overweight and obese Americans age 45 and older have low bone mass (total hip BMD between 1 and 2.5 SD below the young reference mean), and many osteoporotic fractures occur at those levels of BMD. (64,65) Within these higher BMI categories, the prevalence of osteoporosis and low bone mass was higher in women than men and higher in whites and Mexican Americans than in African Americans (Fig. 3).…”
Section: Low Bmd As a Risk Factor For Fracture In Those With High Bmimentioning
confidence: 97%
“…(63) In relation to fracture risk, it is important to note that only 6% of fracture cases are estimated to have osteoporosis (BMD more than 2.5 SD below the reference mean). (64) Our evaluation of National Health and Nutrition Examination Survey (NHANES III) data (Fig. 3, Table 1) revealed that approximately one-third of overweight and obese Americans age 45 and older have low bone mass (total hip BMD between 1 and 2.5 SD below the young reference mean), and many osteoporotic fractures occur at those levels of BMD.…”
Section: Low Bmd As a Risk Factor For Fracture In Those With High Bmimentioning
confidence: 99%
“…Although themselves asymptomatic, the sequelae of osteoporosis and osteopenia in terms of fractures can have a profound impact on patients. Although fractures have a higher incidence in osteoporotic patients than those with osteopenia, the majority of low-impact fractures occur in people with osteopenia [79] and therefore it may be prudent to intervene at less severe levels of bone density than is currently standard practice. Vertebral fractures are common in COPD [80] and lead to significant decrements in lung function from extrathoracic restriction and pain.…”
Section: Low Bone Mineral Density and Fracture Riskmentioning
confidence: 99%
“…Currently the gold standard for measuring BMD is through the use of dual energy X-ray absorption (DEXA). Unfortunately DEXA is not without limitations and is arguably a poor predictor of fracture, with a study carried out by Wainwright et al showing that 54% of new hip fractures occurred in women who did not have osteoporosis as determined by their BMD [7] and data from the National Osteoporosis Risk Assessment, showed that 82% of post-menopausal women with fractures had bone of 'normal' BMD [8]. The limitation of DEXA was perhaps highlighted with the development of FRAX, the World Health Organisation (WHO) fracture assessment tool, which uses BMD along with clinical risk factors and country-specific fracture and mortality data to quantify a patient's 10-year probability of a hip or major osteoporotic fracture [9].…”
Section: Introductionmentioning
confidence: 99%